2010
DOI: 10.1111/j.1095-8312.2010.01487.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological differentiation and reproductive isolation of two closely related sympatric species of Oenanthe (Apiaceae)

Abstract: Oenanthe conioides is a lower Elbe endemic plant species growing in the freshwater tidal zone around Hamburg (Germany). Its closest relative Oenanthe aquatica is widely distributed in Eurasia and grows in calm and shallow freshwater. The two species differ in habitat requirements but are otherwise sympatrically distributed, suggesting that ecological divergence has to be maintained in the face of gene flow. In the present study, we investigated ecological differentiation and reproductive isolation in these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…In congruence with recent studies revealing prezygotic reproductive isolation based solely on extrinsic, ecological barriers (Westberg et al 2010;Melo et al 2014), our example of H. pusillum and H. veselskyi clearly shows that spatial separation of populations and adaptive phenotypic differentiation may confer a strong reduction in gene flow, which is especially significant at the onset of speciation, when intrinsic barriers are not yet in place. However, reproductive isolation solely based on environmentally, extrinsic barriers may be sensitive to environmental changes and subsequent vegetation shifts; only completion of reproductive isolation by endogenous mechanisms may on the long term ensure the stability of the diverging taxa.…”
Section: Discussionsupporting
confidence: 90%
“…In congruence with recent studies revealing prezygotic reproductive isolation based solely on extrinsic, ecological barriers (Westberg et al 2010;Melo et al 2014), our example of H. pusillum and H. veselskyi clearly shows that spatial separation of populations and adaptive phenotypic differentiation may confer a strong reduction in gene flow, which is especially significant at the onset of speciation, when intrinsic barriers are not yet in place. However, reproductive isolation solely based on environmentally, extrinsic barriers may be sensitive to environmental changes and subsequent vegetation shifts; only completion of reproductive isolation by endogenous mechanisms may on the long term ensure the stability of the diverging taxa.…”
Section: Discussionsupporting
confidence: 90%
“…Such species may be particularly vulnerable to habitat fragmentation (Aavik et al 2014). Besides, O. aquatica is a colonizer species experiencing localized extinction/recolonization events (Westberg et al, 2010;Westberg and Kadereit, 2014; L. Favre-Bac, pers. obs.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that compensation in C. thyrsoides was generally strong and that the response to the herbivory simulation did not differ between the subspecies for most traits (Table 2), suggesting either (a) that any contrasting herbivory pressure between the habitats of the two subspecies did not lead to genetic differentiation in these traits or (b) that the two habitats did not differ in herbivory pressure. Suzuki (2008) similarly found no differences in plasticity in response to clipping in a common garden experiment among three populations of the annual Persicaria longiseta with different long-term deer grazing histories, and Rotundo and Aguiar (2008) likewise observed similar tolerance to defoliation among three populations of Poa ligularis differing in recent sheep grazing histories, although other studies do report differences among varieties or closely related species in response to herbivory simulation (Welter and Steggal 1993;Westberg et al 2010). It may be that herbivory thresholds, above which plant performance is differentially affected in the subspecies, have not been reached in our experiment (Strauss and Agrawal 1999).…”
Section: Herbivorymentioning
confidence: 95%